Refraction Seasonal Variation and that Influence on to GHz Range Microwaves Availability - Serdega, V.; Ivanovs, G. (Elektronika ir Elektrotechnika, 2007)
Microwave transmission can be affected by deep fading, which can cause bit errors or even transmission loss. It happened when the Rx (receiving) signal is produced by a large number of components (vectors with random phases), then the Rx power level is variable with Rayleigh statistics. It depend from seasonal variations of refractivity index. Aim of this scientific work was to estimate refractivity index variations during the last 10 years and depending from geographical position of observed region (coastal, continental). Also we compare obtained result with ITUR recommendations. Ill. 4, bibl. 11 (in English, summaries in English, Russian and Lithuanian).